2018
DOI: 10.1002/ajh.25107
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic model identifies patients aged 80 years and older with diffuse large B‐cell lymphoma who may benefit from curative treatment: A multicenter, retrospective analysis by the Spanish GELTAMO group

Abstract: The means of optimally managing very elderly patients with diffuse large B-cell lymphoma (DLBCL) has not been established. We retrospectively analyzed 252 patients aged 80-100 years, diagnosed with DLBCL or grade 3B follicular lymphoma, treated in 19 hospitals from the GELTAMO group. Primary objective was to analyze the influence of the type of treatment and comorbidity scales on progression-free survival (PFS) and overall survival (OS). One hundred sixty-three patients (63%) were treated with chemotherapy tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ from studies utilizing comorbidity indices, e.g. [18][19][20][21][22][23][24][25] , and covered mostly elderly patients, which could have allowed only for speculation on the impact of diabetes in all DLBCL patients (including younger patients). Therefore, we launched a retrospective study to determine the impact of DMT2 on the outcomes of DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ from studies utilizing comorbidity indices, e.g. [18][19][20][21][22][23][24][25] , and covered mostly elderly patients, which could have allowed only for speculation on the impact of diabetes in all DLBCL patients (including younger patients). Therefore, we launched a retrospective study to determine the impact of DMT2 on the outcomes of DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of 46 studies reported 3-year OS for novel prognostic models, while OS was calculated from Kaplan-Meier curves for the rest 3,9,10,16,31,34,35,39,40,44,52,[56][57][58][59] (Tables 1-3). Only the minority of studies (six of 46) reported 3-year OS for compared indices.…”
Section: Difference and Ratio In 3-year Overall Survival Between Riskmentioning
confidence: 99%
“…Similar limitation was found in one retrospective analysis from a multicenter study. Although this retrospective analysis showed that R-CHOP or R-CHOP like regimens improve the overall survival in patients aged 80 years and older with DLBCL or grade 3B follicular lymphoma, their reference group was palliative care, which failed to demonstrate the additional benefit of rituximab [6]. Because rituximab may increase the incidence of opportunistic infections, [7] the benefits associated with the addition of rituximab remain debatable in the treatment of DLBCL patients older than 80 years.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the role of anthracycline remains debatable in DLBCL patients older than 80 years. Three retrospective studies showed that adding anthracycline did not influence overall survival in DLBCL patients older than 80 years [6,9,10].…”
Section: Introductionmentioning
confidence: 99%